Hubungan Entreperneur Self-Efficacy dengan Hardiness terhadap Pemuda dalam Kewirausahaan di Masa Pandemi - Zuliani, Siti; Sa’adah, Sa’adah; Huda, Mariatul (EXERO : Journal of Research in Business and Economics, 2024)
This study aims to determine the level and relationship of entrepreneur self-efficacy and hardiness. In line with the objectives of this research, this research uses quantitative research methods. The research subjects were 150 youths. The method of data collection is by distributing questionnaires. With the data management method using descriptive analysis and correlation test. The results of this study that youth have a high level of entrepreneurial self-efficacy or entrepreneurial self-efficacy. This is obtained from the data, namely youth with a high category of self-efficacy in entrepreneurship as many as 74 people. The data obtained shows relevance to the factor, namely the pressure obtained due to the pandemic period causing youth to have self-initiation against the conditions experienced. Therefore, the entrepreneurial attitude dimensions of self-efficacy and hardiness are needed for the formation of strong and confident entrepreneurs, especially during a pandemic which requires taking risks when economic growth declines.